Kaldor-Verdoorn's Law and increasing returns to scale: A comparison across developed countries - Emanuele Millemaci; Ferdinando Ofria (Fondazione Eni Enrico Mattei (FEEM), 2012)
The objective of this study is to investigate the validity of the Kaldor-Verdoorn's Law in explaining the long run determinants of the labor productivity growth for the manufacturing sector of some developed economies (Western European Countries, Australia, Canada, Japan and United States). We consider the period 1973-2006 using data provided by the European Commission - Economics and Financial Affairs. Our findings suggest that the law is valid for the manufacturing as countries show increasing returns to scale. Capital growth and labor cost growth do not appear important in explaining productivity growth. The estimated Verdoorn coefficients are found to be substantially stable throughout the period.
Keywords: C32; O47; O57; 330; Increasing Returns; Kaldor-Verdoorn Law; Productivity Growth; Manufacturing Sector; Verarbeitendes Gewerbe; Arbeitsproduktivität; Verdoorn's Law; Skalenertrag; Industriestaaten